A new Anathallis (Orchidaceae: Pleurothallidinae) from the Brazilian Amazon - Pessoa, Edlley; Alves, Marccus (Phytotaxa, 2012)
A new species of Anathallis is described from the Brazilian Amazon, state of Amazonas. It is known only from the central Amazon. The unlobed lip distinguishes it from morphologically related species.